Introduction to Sustainable Finance. Context, questions and areas for research - Gonçalves, V. (Exchange Week for Erasmus + visiting professors at Iscte Business School, 2022)
Introduction to Sustainable Finance. Context, questions and areas for research The context 1. Physical risks 2. Transition risks 3. Impacts on reputation 4. Regulation pressure 5. Consumer pressure 6. Pressure of technological evolution 7. Impacts of the European Green Deal on business Questions: 1. Any knowledge about the real impact of the sustainability issue on the national market of different countries? 2. What are the main lines of research? 3. More ESG risk => higher cost of capital ? 4. ESG investing: what impact on corporate behavior and on asset performance and yield? 5. Are there short term transition costs and long term benefits? 6. How to incorporate ESG in the investment process? A non-financial information standard is still lacking. But more policy responses and new technologies emerge 7. What ESG information is needed? 8. What non-monetary benefits? 9. What role for regulation and asset managers? 10. How to define appropriate sustainability strategies for companies (and for FIs) that mediate competitive advantages and performance? 11. What financing strategies for sustainability? Theoretical questions/Areas for research 1. Internalization of externalities in investment decisions and performance measures 2. Investment decisions based on “value drivers” of companies based on strategic and risk analysis in the context of the environmental and digital transition 3. Different sectors with different socio-economic transitions and companies with different transition capacities and different long-term value potential. 4. Qualitative research on how the market appreciates green and sustainable practices 5. Reformulation of portfolio theory / to a new, more integrative Financial Theory a) Potential for diversification - More income types (with financial and non-financial accounting) - More risk classes (ESG) b) Time - Temporal effect of financial, environmental and social analysis (Traditional finance as a special case, with narrow set of the aspects mentioned)